FAKTOR-FAKTOR YANG MEMPENGARUHI TERJADINYA ANEMIA PADA IBU HAMIL TRIMESTER II - Damanik, Syahroni (Jurnal Ilmiah Ilmu Kesehatan: Wawasan Kesehatan, 2019)
The World Health Organization (WHO) in 2015 is estimated as many as 52.5% of pregnant women in Southeast Asia who experience anemia. 3,4 in various countries, including Indonesia, reported that the incidence of anemia is still high. To prove determine the affecting factors to the occurrence of anemia in trimester II pregnant women at Kutalimbaru Health Center, Deli Serdang District in 2018. Tyfe of research design was an analytical survey with a cross sectional approach. The population of this study was trimester II pregnant women who had not come to Kutalimbaru Health Center in 2018 totaling 33 people (Accidental sampling.). The data used was primary data and secondary data. The instruments used were checklist and questionnaire with 12 questions. The data analysis were univariate, bivariate analysis using Chi-square test. The study found results of the study 33 respondents, there was no effect of knowledge with the occurrence of anemia in pregnant women in second trimester p value = 0.056 <0.05 with OR 5.417 (95% CI), there was an effect of parity with the occurrence of anemia in pregnant women in second trimester obtained p = 0.053 <0.05 with OR 6.286 (95% CI), there was a economic effect with the occurrence of anemia in pregnant women in second trimester obtained p value = 0.006 <0.05 with OR 13,000 (95% CI). There is no effect of knowledge with the occurrence of anemia in pregnant women in second trimester at Kutalimbaru Health Center, parity and economy with the occurrence of anemia in pregnant women in second trimester at Kutalimbaru Health Center.